A Meta-Analysis of the Relationship between Testicular Microlithiasis and Incidence of Testicular Cancer - Wang, Tao; Liu, LuHao; Luo, JinTai; Liu, TaiSheng; Wei, AnYang (Urology Journal, 2015)
Purpose: There are many recent observational studies on testicular microlithiasis (TM) and risk of testicular cancer. Whether TM increases the risk of testicular cancer is still inconclusive. The objective of this updated meta-analysis was to synthesize evidence from clinical observational studies that evaluated the association between TM and testicular cancer. Materials and Methods: We identified eligible studies by searching the PubMed, Embase and Cochrane Library before March 2014. Adjusted relative risks (RR) with 95% confidence interval (CI) were calculated using random-or fixed-model. Results: A total of 14 studies involving 35578 participants were included in the meta-analysis. On the basis of the Newcastle Ottawa Scale systematic review, eleven studies were identified as relatively high-quality. TM was strong association with an increased incidence of testicular cancer (RR = 12.70, 95% CI: 8.18-19.71, P < .001), with significant evidence of heterogeneity among these studies (P for heterogeneity < .001, I2 = 82.1%). The subgroup and sensitivity analysis confirmed the stability of the results and no publication bias was detected. Conclusion: The present meta-analysis suggests that TM is significantly associated with risk of testicular cancer. More researches are warranted to clarify an understanding of the association between TM and risk of testicular cancer.